Counter-Hegemony and Plurarity of Knowledges in Education in the Light of Socio-Poetics - Monaliza Holanda dos Santos; Eugênia de Paula Benício Cordeiro (Universidade Federal do Rio Grande do Sul, 2021)
This article aims to present methodological underpinnings of Socio-poetics research connected to education; more specifically, to rethink inter and transculturality envisioning knowledge decolonization, as well as, to describe the five Socio-poetics research methods basic orientation. Our studies point out that Socio-poetics, by acknowledging plurality and diversity of knowledge, can contribute to broaden horizons, when it refers to transculturality, of contemporary educational areas characterized by diversity as well as individuals' singularities, as long as it embraces counter-hegemonic perspectives and conceptions in the process of knowledge development.